Creating Organizational Soul. - Bellingham, Richard (HRD Press, 2010)
Does your organization have soul? Are you passionate about a higher purpose? Do you engage in meaningful dialogue? Are you caring and compassionate? Do you spend time reflecting on critical issues? People in soulful organizations are able to say they demonstrate these behaviors everyday. You can become one of those people by following the advice and guidance in this innovative book. Creating Organizational Soul makes a compelling case for the strong connection between organizational soul and productivity, innovation and results. The intent of the book is to get leaders to take a hard look at w.